PERAN BRAND AWARENESS MEMEDIASI DAYA TARIK IKLAN TERHADAP BRAND ATTITUDE INDOMIE DI KOTA DENPASAR - Pratiwi, Wayan Arisna; Rahanatha, Gede Bayu (E-Jurnal Manajemen; Vol 5 No 12 (2016), 2017)
The aim of this research was explain the mediating role of brand awareness on the effect of advertising appeal towards brand attitude of Indomie instant noodles in Denpasar City. The population used are the Indomie’s consumer in Denpasar City. Samples determined by purposive sampling method as 110 respondents were taken. The data were collected through questionnaires and analyzed by path analysis and sobel test technique. The results indicate that advertising appeal and brand awareness of each has significantly positive effect on brand attitude and also the mediating role of brand awareness that can strengthen the relationships between advertising appeal and brand attitude. It is recommended for Indomie management to strengthen the appeal of their advertisement in order to maintain consumers’ positive attitude towards the brand through the high level of brand awareness.
Keywords: advertising appeal, brand awareness, brand attitude